2004
DOI: 10.1074/jbc.m400541200
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylesterase 3 (EC 3.1.1.1) Is a Major Adipocyte Lipase

Abstract: Hydrolysis of triglycerides is central to energy homeostasis in white adipose tissue (WAT). Hormone-sensitive lipase (HSL) was previously felt to mediate all lipolysis in WAT. Surprisingly, HSL-deficient mice show active HSL-independent lipolysis, suggesting that other lipase(s) also mediate triglyceride hydrolysis. To clarify this, we used functional proteomics to detect non-HSL lipase(s) in mouse WAT. After cell fractionation of intraabdominal WAT, most non-HSL neutral lipase activity is localized in the 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 27 publications
4
94
0
1
Order By: Relevance
“…The expression of HSL in beta cells, however, has been shown to be upregulated by a prolonged high glucose concentration [32] and HSL has been shown to be co-localised with insulin granules [33]. There has been particular interest in the role of non-HSL lipases in adipose tissue metabolism [34,35]. The roles of these alternative lipases in the islet also warrant investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of HSL in beta cells, however, has been shown to be upregulated by a prolonged high glucose concentration [32] and HSL has been shown to be co-localised with insulin granules [33]. There has been particular interest in the role of non-HSL lipases in adipose tissue metabolism [34,35]. The roles of these alternative lipases in the islet also warrant investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies that utilized in vitro assays and organ cultures of murine WAT have shown that, together, desnutrin/ATGL and HSL are responsible for more than 95% of the TAG hydrolase activity in murine WAT [79]. However, additional TAG lipases, including triacylglycerol hydrolase (TGH) [80], TGH2 [81], as well as the patatin-domaincontaining proteins, GS2 and GS2-like [76], have been identified in adipocytes, but their role in adipocyte lipolysis requires further investigation.…”
Section: Hydrolysis Of Triacylglycerolmentioning
confidence: 99%
“…Triacylglycerol hydrolase (TGH) is highly expressed in liver and adipose tissue and has been suggested to represent a major adipocyte lipase (5). The recently identified TGH-2 exhibits high homology to TGH and a similar tissue distribution pattern (6).…”
mentioning
confidence: 99%